Novel tetrahydrocurcumin integrated mucoadhesive nanocomposite κ-carrageenan/xanthan gum sponges: a strategy for effective local treatment of oral cancerous and precancerous lesions - Shimaa A. Elbanna; Heba M. K. Ebada; Ossama Y. Abdallah; Marwa M. Essawy; Hend M. Abdelhamid; Hebatallah S. Barakat (Taylor & Francis Group, 2023)
AbstractOral cancer is one of the leading causes of death worldwide. Oral precancerous lesions (OPL) are the precursors of oral cancer, with varying degrees of progression. Tetrahydrocurcumin (THC) is a major metabolite of curcumin with superior anticancer properties against various types of cancer. However, THC's clinical outcome is limited by its poor aqueous solubility. Herein, we developed novel mucoadhesive biopolymer-based composite sponges for buccal delivery of THC, exploiting nanotechnology and mucoadhesion for efficient prevention and treatment of oral cancer. Firstly, THC-nanocrystals (THC-NC) were formulated and characterized for subsequent loading into mucoadhesive composite sponges. The anticancer activity of THC-NC was assessed on a human tongue squamous carcinoma cell line (SCC-4). Finally, the chemopreventive activity of THC-NC loaded sponges (THC-NC-S) was examined in DMBA-induced hamster OPL. The selected THC-NC exhibited a particle size of 532.68 ± 13.20 nm and a zeta potential of −46.08 ± 1.12 mV. Moreover, THC-NC enhanced the anticancer effect against SCC-4 with an IC50 value of 80 µg/mL. THC-NC-S exhibited good mucoadhesion properties (0.24 ± 0.02 N) with sustained drug release, where 90% of THC was released over 4 days. Furthermore, THC-NC-S had a magnificent potential for maintaining high chemopreventive activity, as demonstrated by significant regression in the dysplasia degree and a decline in cyclin D1 (control: 40.4 ± 12.5, THC-NC-S: 12.07 ± 5.2), culminating in significant amelioration after 25 days of treatment. Conclusively, novel THC-NC-S represent a promising platform for local therapy of OPL, preventing their malignant transformation into cancer.